The dynamics of poverty and its consequences on regional inequalities in Romania - Marinela ISTRATE (Eastern Journal of European Studies, 2018)
Poverty has raised growing interest due to its various spatial aspects and implications. The purpose of this paper is to highlight the relationship between poverty and inequality, analysing the way in which a high degree of social and economic inequality influences the different forms of poverty manifestation. We made use of a three-dimension analysis: actual poverty (as expressed by absolute and relative thresholds), inequality of income distribution and regional distribution of these phenomena. Although poverty has diminished, the feeling of poverty remains strong both in relation to the income of other co-nationals and to that of other European countries, Romania continuing to be, unfortunately, one of the poorest countries in EU-28. The investigation carried out revealed the fact that the economic development of the country has been accompanied by a fast decrease in absolute poverty but also by a slight increase in relative poverty.